Breaking the news how the media undermine American democracy - Fallows, James
Why do Americans mistrust the news media? It may be because show like "The McLaughlin Group" reduce participating journalists to so many shouting heads. Or because, increasingly, the profession treats issues as complex as health-care reform and foreign policy as exercises in political gamesmanship. Or because muckrackers have given way to "buckrakers" who command huge fees lecturing to the very interest groups they are supposed to cover.